PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AQIDAH AKHLAK DI KELAS IV MADRASAH IBTIDAIYAH AL MAWADDAH WARRAHMAH KOLAKA - Wanni Agustin; Abd. Haris Nasution; Muhammad Asra (Jurnal Teknologi Pendidikan Madrasah, 2025)
The implementation of learning in MI Al Mawaddah Warrahmah Kolaka can be said to be less varied and monotonous. This is as the results of a preliminary survey conducted previously on class IV MI Al Mawaddah Warrahmah Kolaka. 46% of learners stated that the learning process that is carried out in the same way continuously and also does not involve media makes them bored and tends to get bored. This certainly affects students' learning outcomes if there is no follow-up to this problem. The problems that can be raised in this study are how the form of learning methods used in Madrasah Ibtidaiyah Al Mawaddah Warrahmah Kolaka? and how the application of the Mind Mapping method to improve learning outcomes in the subject of aqidah akhlak in class IV MI Al Mawaddah Warrahmah Kolaka. while the purpose of this study is to find out how the form of learning methods used in Madrasah Ibtidaiyah Al Mawaddah Warrahmah Kolaka. and to find out the improvement of student learning outcomes through the Mind Mapping method of class IV MI Al Mawaddah Warrahmah Kolaka.The research methods used include the type of research in the form of Classroom Action Research (PTK); the research subject is class IV students of MI Al Mawaddah Warrahmah Kolaka Kec. Kolaka Kab. Kolaka; research procedures carried out include four stages namely planning, implementation, observation and reflection; research instruments in the form of observation sheets for teachers and students and test scoring sheets; data analysis techniques in the form of observation data analysis and test analysis.The results showed that the forms of learning methods used in Madrasah Ibtidaiyah Al Mawaddah Warrahmah Kolaka were lecture, question and answer and discussion methods. The application of the mind mapping method in aqidah akhlak subjects has increased the learning outcomes of students, where in the pre-cycle the achievement of student learning completeness is 42% with an average score of 68.3, cycle I achievement of student learning completeness is 83% with an average score of 84.16 while in cycle II the achievement of student learning completeness is 92% with an average score of 87.5.